The Effect of Picture And Picture Type Cooperative Learning Model on Social Science Learning on Cognitive Learning Outcomes of Grade IV Students at SDN Tanjung Jati 2 Kamal - Firanti, Retno Maya Sealviana; Setyawan, Agung; Kurniasih, Nila (eductum: Jurnal Literasi Pendidikan, 2025)
The study aims to determine the effect of the cooperative learning model of Picture And Picture type on the cognitive learning outcomes of fourth grade students at SDN Tanjung Jati 2. This study also uses a Quasi Experimental Design research type, the type of research design used in this study is Nonequivalent Control Group Design using pretest and posttest on the control class and the experimental class. The samples used were class IV of SDN Tanjung Jati 2 as the experimental class and class IV of SDN Banyuajuh 2 as the control class. In this study, the researcher used the Independent t-test which was used to compare students in the control class and the experimental class. The control class is a class that is not given treatment or action while the experimental class is a class that is given treatment or action in the form of implementing the Cooperative learning model type Picture And Picture. The significance value obtained is 0.041 and 0.049, the value is less than 0.05, so the decision criteria are Ho is rejected and Ha is accepted. These results indicate that the Cooperative learning model type Picture And Picture has an effect on the learning outcomes of fourth grade students. It is known that in the pretest value of the control class of 20 students, there were 5 students who completed it with an average of 45, while in the experimental class of 23 students, there were 11 students who completed it with an average of 51. In the posttest value of the control class of 20 students, all students completed it with an average of 77, while in the experimental class of 23 students, all students completed it with an average of 84.